Interview with Felice Parise - Pilkington, Rosemarie (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> <![endif]–> In Chapter 23 of my book The Spirit of Dr. Bindelof: The Enigma of Séance Phenomena, (Pilkington, 2006) I called Felicia Parise " A Mini Kulagina." I had read about this remarkable woman and had heard much about her from mutual friends and colleagues who had worked with her but nobody seemed to know where she was or what had become of her. So my chapter was written without ever having met her. What I knew was that she had worked at Maimonides Hospital in Brooklyn, New York at the time Montague Ullman, Stanley Krippner and Charles Honorton were conducting experiments in Dream Telepathy there (Ullman, Krippner and Vaughan, 1973), that she had volunteered to participate in the program and turned out to be one of their best subjects. She was discovered have strong clairvoyant and telepathic abilities and was willing to work with researchers. When Ullman returned from a visit to the then U.S.S.R., where he witnessed and examined Nina Kulagina, who was being studied by Russian scientists for her ability to move objects, deflect compasses and affect even excised frogs hearts, he brought back a film showing some of her feats. In addition to Honorton and Krippner, a professional magician and members of the lab including Felicia attended the showing. Most of those present doubted Kulagina's ability and speculated on how she might be performing some trick. Felicia, however, believed her to be genuine and decided to try to learn to move small objects as well, which after a long time and much effort she did. [See Pilkington, (2006) and especially Honorton (1993) for a detailed, informative and amusing account.] Felicia participated in many successful PK experiments but eventually gave up her activities because of the physical toll they exacted. At least that was the reason given in most on-line searches. But perhaps it's really because Felicia is a very private person who was bothered by the inevitable doubting and questioning of those who could not accept the evidence. I had tried unsuccessfully on my computer to locate her several times, but one day to my amazement a friend discovered both her Manhattan address and telephone number! It seems she had for years kept her number unlisted but perhaps tired of paying the attached fees allowed it to be published and we were able to get the information. (She has since withdrawn its publication.) I first wrote to her then phoned her and she was very gracious. Since she was coming to Staten Island, where I live, to visit relatives, she visited me at my apartment where I took this snapshot: We sat down for her interview in August, 2013 but didn't get together to go over the transcript, clarify questions etc. until the summer of this year, 2014. I am grateful to Felicia for sharing her experiences with us. We can all learn a lot from her. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>